To respond or not to respond: exploring empathy-related psychological and structural brain differences between placebo analgesia responders and non-responders - Hartmann, Helena; Banwinkler, Magdalena; Riva, Federica; Lamm, Claus (Frontiers in Psychology, 2023)
Introduction Placebo responsiveness is highly variable across individuals. In the domain of pain, it may range from pronounced hypoalgesia to no response at all. Which factors predict such variation awaits clarification, as the available literature is characterized by mixed and inconclusive results. Particularly interesting in this case are social factors such as empathy or prosocial behavior, as prior work has stressed the connection between feeling pain yourself and empathizing with pain observed in others. Methods In a mixed confirmatory and exploratory approach, this study investigated potential psychological and structural brain differences between placebo responders and non-responders in the domain of pain. We aggregated data of four behavioral and neuroimaging studies that had been designed to investigate the effects of placebo analgesia on empathy. Results Analyses comparing groups of placebo responders and non-responders showed significant group differences in trait characteristics, with responders reporting increased helping behavior and lower psychopathic traits compared to non-responders. Uncorrected results further showed higher pain-related empathic concern in responders vs. non-responders. These results were accompaniedby tentative group differences in brain structure: placebo analgesia non-responders exhibited increased gray matter volume in left inferior temporal and parietal supramarginal cortical areas, and an increased cortical surface area in bilateral middle temporal cortex. Discussion Together, our findings suggest that modifiability of one’s pain perception by means of placebo effects is linked to personality traits characterizing social emotions and behavior. They also hint that these psychological as well as brain structural characteristics might be beneficial for the identification of placebo responders. At the same time, they stress the importance of considering contextual factors such as the study setting or paradigm when investigating the association between individual characteristics and placebo responding.